Problemy wdrażania controllingu w przedsiębiorstwach województwa warmińsko-mazurskiego - Dynowska, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The system of controlling and management accounting doesn't solve directly all problems appearing in a firm but it reveals them. Due to the better awareness of costs it's possible to reduce them. The application of some controlling instruments in the analyzed firms of consumable and meat branch enabled most of them to realize their aims and lower their costs. It also improved the cooperation between departments within the firms as well as the information flow, thus making the firms more efficient and competitive on the market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 68-77